2011
DOI: 10.1089/fpd.2010.0749
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Foodborne Salmonellosis in Rural KwaZulu-Natal, South Africa

Abstract: The results suggest a foodborne Salmonella Enteritidis outbreak due to contaminated food served at the school function. Epidemiological investigations continue to be extremely difficult in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 9 publications
(10 reference statements)
0
28
0
Order By: Relevance
“…Antimicrobial resistant Salmonella is one of the global problems in present day clinical practices and recently, a strain on the verge of pan-resistance was reported [2]. In sub-Saharan Africa (SSA), the prevalence of MDR Salmonella has increased and outbreaks due to MDR strains were recorded [3-5]. Infections with MDR pathogens are associated with excess morbidity and mortality probably because of the co-selection of traits of drug resistance and virulence [6].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistant Salmonella is one of the global problems in present day clinical practices and recently, a strain on the verge of pan-resistance was reported [2]. In sub-Saharan Africa (SSA), the prevalence of MDR Salmonella has increased and outbreaks due to MDR strains were recorded [3-5]. Infections with MDR pathogens are associated with excess morbidity and mortality probably because of the co-selection of traits of drug resistance and virulence [6].…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, the MDG (Millennium Development Goals) 2013 report pointed out that some 3-5 million people still depend on untreated water from rivers and springs (UN, 2013). An epidemiological study by Niehaus et al (2011), following an outbreak of food-borne salmonellosis after a school function in Durban, KwaZulu-Natal, reported that Salmonella enteritidis isolated from patients and food samples could not be distinguished phenotypically and genotypically. The authors suggested a point-source as the origin of the outbreak, with a possibility of continued transmission through the water supply.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella Enteritidis generally causes human illness with typical symptoms including fever, vomiting, diarrhea, and abdominal cramps within 12-72 h after ingestion of contaminated food (CDC, 2010). However, only 3% of Salmonella-related foodborne disease is confirmed and reported to surveillance systems (Niehaus et al, 2011). On May 30, 2013, 96 patients from the same company in Ningbo, China acquired gastroenteritis and sought medical advice in local hospitals.…”
Section: Introductionmentioning
confidence: 99%